The inductive-effect of electron withdrawing trifluoromethyl for thermally activated delayed fluorescence: tunable emission from tetra- to penta-carbazole in solution processed blue OLEDs1. Issue 65 (21st August 2015) - Mei, Ling; Hu, Jia; Cao, Xudong; Wang, Fangfang; Zheng, Chao; Tao, Youtian; Zhang, Xinwen; Huang, Wei
<x xml:space="preserve">Abstract</x> Non-conjugated trifluoromethyl was introduced as a new acceptor in TADF OLEDs. 5CzCF3Ph exhibited significantly higher efficiency than 4CzCF3Ph due to its lower ΔEST value.